An insight into pineapple peel waste adsorbent for iron contaminated water through kinetic and isotherm study - Nurul Faizah, Abd Ghapar; Rozaimi, Abu Samah; Mohamad Syafiq, Abdul Wahab; Sunarti, Abd Rahman; Mohd Hafiz Dzarfan, Othman (Universiti Kebangsaan Malaysia, 2024)
The swift growth of sectors like steel and coal mining leads to a higher release of heavy metals like iron into aquatic ecosystems, resulting in water pollution. In this study, the kinetics and isotherms studies were applied to pineapple peel waste based adsorbent for iron removal. An adsorbent derived from discarded pineapple peels was created through a chemical activation process, employing zinc chloride (ZnCl2) as the activator. By examining the effects of various experimental parameters, including contact duration (30–240 min), concentration of iron (5–80 ppm), and the amount of adsorbent (2–24 g/L), the behaviour of the adsorbent for iron adsorption was carefully studied. Maximum iron removal of 99.24% efficiency with adsorbent dosage of 20 g/L was achieved through this study. The iron removal process was most accurately represented by the Freundlich isotherm model, exhibiting an R2 value of 0.985. Furthermore, the kinetics investigation demonstrated an excellent fit with the pseudo-second-order model for iron adsorption, yielding an R2 value of 0.999. These findings strongly indicate that pineapple peel waste holds promise as a viable adsorbent for eliminating iron from water bodies.